Use of the impact index to interpret the influence of factors that influence on the age at incorporation to the female Charolaise reproduction - Vega, A. M.; Herrera, R. S.; Torres, Verena; Lamela, L.; Sierra, I.; Santana, A.; Cino, Delia M.; Cabrales, Cecilia (Cuban Journal of Agricultural Science, 2021)
An experiment was designed at Empresa de Genética y Cría “Manuel Fajardo, Granma, Cuba, to evaluate the silvopastoral system of Leucaena leucocephala cv. Peru and Cynodon nlemfuensis compared with monoculture grassland of the referred grass in Cuban Charolaise heifers. The analytical methodology for measuring the impact index was used. The results showed the preponderance of the factors initial weight, weight gain, weight gain per day, starting age and incorporation age, availability of biomass, rainfall and temperature. The indicators of the first component had the highest impact index on silvopastoral technology. They reflected lower value in monoculture, with negative figures. In the first impact index, 33.8 % of the most preponderant indicators were found in the principal components analysis. The best live weight gains (0.55 kg.animal.day-1) and incorporation age to the females reproduction (19 months) were obtained in the silvopastoral system with Leucaena and the financial indicators were higher in this system. This result showed a closer relation between the weight and the gains of the animals with the incorporation age. It is concluded that the mathematical methods used (measurement of the impact index) were adequate to establish the superiority of the silvopastoral system compared to the grass monoculture when obtaining higher weight, lower incorporation age and satisfactory economic balance of the female Charolaise. Key words: impact index, multivariate analysis, incorporation age, Charolaise